Millennial Motivation and Engagement - Sharma, Tanya (2018)
Millennials, also referred to as Generation Y compose the largest proportion of the global workforce today and would form over 50% of the working population by as soon as 2020. Millennials are accused of being casual, individualistic, consumeristic, and materialistic, while they are also appreciated for being the most well-educated generation in history, technologically advanced, loyal, and socially responsible. This dissertation aims to understand their behaviours, points of view, and the values they believe in, to gauge what they are like at work. A review of the literature on motivation theories and generation theories reveals that there exists a gap in the theories, and that further research needs to be carried out to upgrade them to incorporate the value systems, contexts, and mindsets of the younger generations.